NEUROMODULATION OF THE PRIMARY MOTOR CORTEX BY rTMS AND TREADMILL WALKING TRAINING IN CHILDREN WITH SPASTIC CEREBRAL PALSY: RANDOMIZED CONTROLLED DOUBLE-BLIND CLINICAL TRIAL (CIPEEX, 2025)
The objective of the study project is to compare the effects of ten sessions of treadmill gait training conducted after 20 minutes of rTMS application on the primary motor cortex, both active and placebo, in the domain of Activity (gait, functional mobility, functional balance, and gross motor function) and Participation of the ICF in children with spastic CP. This is a randomized, placebo-controlled, double-blind clinical trial involving 34 children diagnosed with spastic CP. The participants will be evaluated one week before, one week after, and one month after the end of the intervention, using the Modified Ashworth Scale, Tardieu Scale, Muscle Strength Assessment, motor evoked potential, Timed Up and Go, Walk Test, Berg Balance Scale, Gross Motor Function Measure, and Participation and Environment Measure - Children and Youth. The experimental group will perform treadmill gait training after the application of active rTMS on the primary motor cortex, and the control group after the application of placebo rTMS. The intervention will involve ten intervention sessions, with a frequency of five sessions per week, conducted over two consecutive weeks and lasting 40 minutes each (20 minutes of rTMS and 20 minutes of treadmill gait training). Considering the potential effect of rTMS on the primary motor cortex, it is expected that the intervention will enhance the effect size of gait training in children with CP.
Keywords: Cerebral palsy; gait; balance; child; physiotherapy; transcranial magnetic stimulation